Identify the Impact of an Innovative Evaluation Strategy on the Care of Babies Having Neonatal Abstinence Disorder - Arslan Khalid, Atifa Rashid, Saddaf Hina, Kinza Tahir, Sumera Abdul Karim, Muhammad Zafar Rana (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The prevalence of neonatal abstinence disorder is increasing, which places a huge strain on the nation’s healthcare infrastructure. It’s possible that using the usual Finnegan Neonatal Abstinence Scoring System diagnostic technique might result in newborns with NAS receiving needless opioid medication. Researchers came up with a whole new evaluation strategy, and in this paper, we will discuss how it influences the treatment of babies who have NAS. Methods: Researchers took a historical look at the therapy choices made for sixty babies who had been exposed to opioids and were being cared for in the inpatient ward at Sir Ganga Ram Hospital in Lahore. While the FNASS scores of all newborns were monitored and recorded every three to seven hours, the Eat, Sleep, and Console assessment strategy were used to control them. Researchers evaluated the actual medical decisions that have been made using the ESC method with the projected treatment decisions that were based on the recorded FNASS scores. The administration of morphine upon delivery was the main outcome. Results: When employing the ESC method, morphine was administered to 8 newborns, which is a sixteen percent success rate. In comparison, the FNASS method predicted that morphine would be administered to 32 infants, which represents a sixty-four percent success rate (P, .002). When compared to the FNASS method’s prediction of 90 days (26.8 percent), the ESC method’s prediction of starting or increasing morphine administration was accurate 10 days (3.8 percent) earlier (P, .002). It was noted there were no other possible complications or readmissions that occurred. Conclusion: The frequency with which morphine was administered to infants who were handled using the ESC strategy was much lower than the frequency with which it will be administered if FNASS approach had been used. The ESC method is an efficient strategy for care of newborns diagnosed through NAS. This method restricts the use of pharmacologic therapy and has the potential to result in significant decreases in the amount of time spent in the hospital. Keywords: Neonatal Abstinence Syndrome, Nation’s Healthcare Infrastructure.